Biology of plant volatiles - Pichersky, Eran; Dudareva, Natalia
"Plants produce volatile compounds for communication within the environment. They play essential roles in pollinator and seed-disperser attraction, defense against pathogens, signaling and stress response. With contributions from distinguished leading scientists in the field, this book provides up-to-date accomplishments in floral scent research"--